If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10y + 7 = 27 Reorder the terms: 7 + 10y = 27 Solving 7 + 10y = 27 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 10y = 27 + -7 Combine like terms: 7 + -7 = 0 0 + 10y = 27 + -7 10y = 27 + -7 Combine like terms: 27 + -7 = 20 10y = 20 Divide each side by '10'. y = 2 Simplifying y = 2
| 5-6+2=1 | | 56=-7(-4+2m)+5(-m-2) | | 2z-14+5z-9+z=180 | | 4=32+7z | | 9x^4(-2x^3-6)= | | -30=-5(8+r)-2(r+2) | | 8*5*0+2=2 | | -10x^2-27x-18=0 | | 4=-(r-5)+11 | | 2(1+5v)+3(v-3)=-59 | | 2(+5v)+3(v-3)=-59 | | Cx+Gy=J | | (x^3+4x^2-x-4)=0 | | 3+1*2=5 | | y=416.72x^2+4416.7x^4+8500 | | 2.9+x=3.83 | | x=.34*90 | | -y^2-10y-16=0 | | 3m^2-5m-2=0factor | | -5y^2+14y-8=0 | | 2(1-1)+3(1-1)=5(1-1) | | -3y^2+3y+60=0 | | 9x-(6x+5)=4x-25 | | 2y-48+2y-46+38=180 | | -2x+42=-138+7x | | 14-1.6(t+6)=4.6 | | f(x)=6x^2+4x+3 | | 3x+10=3x-4 | | 5-9+7+2=5 | | 4x^4-6x^2+4=0 | | 4x-3(3x+2)=49 | | -50=2(3n-7) |